Faktor yang Mempengaruhi Keputusan Pembelian Generasi Z pada Produk Somethinc: Label Halal, Kualitas Produk, dan Electronic Word Of Mouth (E-WOM) - Nur Shobihatul Lailiyah; Mahmudatus Sadiyah (Efektor, 2025)
The purpose of this study is to degree how halal labeling, product quality and electronic word of mouth (e-wom) have an effect on buying choices for Somethinc products. This studies is quantitative in nature the usage of the technology Z population who have used Somethinc products. There were 100 samples used within the study which have been analyzed through SmartPLS model 4.0 software with the PLS-SEM technique. The findings display that the halal label has a high quality and tremendous effect on the choice to purchase, as well as product satisfactory and electronic phrase of mouth which even have a wonderful and sizeable impact on shopping selections. among all the variables, the halal label is the maximum dominant factor influencing the choice to buy. concurrently, the three variables have an effect on purchasing decisions really worth 59,8% at the same time as 40.2% are encouraged by way of variables not examined. those findings offer insights for cosmetics enterprise players to consciousness on improving product first-class to layout greater effective marketing techniques to improve purchasing decisions.